Pengaruh Variasi Temperatur Terhadap Ketangguhan Impact Baja Karbon Rendah Menggunakan Pengujian Charpy - Hutabarat, Adelia Naomi Titi Marsaulina; Suhardiman, Suhardiman; Budiana, Agnes Arum (Jurnal Ragam Pengabdian, 2026)
Low-carbon steel is one of the most widely used engineering materials due to its excellent ductility, good weldability, and ease of fabrication for various industrial applications. However, variations in operating temperature can significantly affect its ability to absorb impact energy, resulting in changes in its mechanical behavior and fracture characteristics. This study aimed to analyze the effect of temperature variation on the impact toughness of low-carbon steel using the Charpy impact test. An experimental research design was employed using low-carbon steel containing 0.159% carbon, as determined by chemical composition analysis. Charpy impact testing was conducted at seven temperature levels: −50°C, −30°C, −10°C, 0°C, 10°C, 30°C, and 50°C. Data were analyzed descriptively by calculating the absorbed impact energy and impact toughness based on the effective cross-sectional area of the specimens. The results showed that increasing temperature significantly improved both absorbed impact energy and impact toughness, with impact energy increasing from 21.28 J at −50°C to 65.27 J at 50°C and impact toughness increasing from 0.387 J/mm² to 1.187 J/mm². These findings indicate that higher temperatures enhance the plastic deformation capability of low-carbon steel, while lower temperatures promote brittle fracture. The novelty of this study lies in providing comprehensive experimental data on the relationship between temperatures ranging from −50°C to 50°C and the impact toughness of low-carbon steel containing 0.159% carbon, providing valuable information for material selection under various service temperature conditions.